The evaluation of printability and nonenzymatic NADH reduction of 4 '-chlorophenylazo-2-naphthol for use as a printing pigment - (:unkn) unknown (OIL & COLOUR CHEMISTS ASSOC, 2005)
The printability of 4'-chlorophenylazo-2-naphthol (CPAN) was evaluated on gloss-coated paper. The preliminary results indicated that the proposed pigment could be used in offset and oil-based ink production. The pigment and its potential reduction product, 4-chloroaniline, were then separated by a reverse phase high-pressure liquid chromatography system. The pigment was incubated with NADH at 37 degrees C for half an hour at different pH values to investigate its possible reduction into the corresponding primary amines (ie 4-chloroaniline and 2-amino-1-naphthol). However, no reduction was observed. This finding indicates a desirable evidence for the pigment in terms of its stability against NADH (nicotinamide adenine dinucleotide), a known biochemical reducing agent in living organisms when the potential toxicity from aromatic primary amines is considered.
Keywords: azo dyes; printing pigments and dyes; azo reduction; PERFORMANCE LIQUID-CHROMATOGRAPHY; AZO DYES; PRODUCTS